Desarrollo rural rostenible y cooperación - Cruz Maceín, José Luis (Revista Española de Desarrollo y Cooperación, 2023)
Rural development is an essential element to poverty reduction in developing countries. This paper offers briefs notes about rural development history in poor countries. The background introduces the current situation, which is presented in international development agencies approaches to resolve this problem, and it explains three important elements in current discourse about rural development: agriculture and food security, land tenancy and access to natural resources and social capital.